Treasure Hunting and Pillaging in Sicily: Acquiring a Deviant Identity - Migliore, Sam (Anthropologica, 2022)
Treasure hunting, the pillaging of archaeological sites and the resultant trade in antiquities have been increasingly subject to negative sanctions both by governments and international bodies. Rural Sicilians, conditioned by a history of exploitation at the hands of out siders to view government regulations with suspicion, do not label treasure hunting as ipso facto deviant. However, if such actions cause damage to property or persons within the community, the perpetrators will be labelled as deviants and will be subjected to formal sanctions in accordance with the unwritten code of omerta ("manliness," respect). A specific ethnographic case is examined in detail.